Assaying cell cycle status using flow cytometry - Kim, Kang Ho (Curr Protoc Mol Biol, 2015)
In this unit, we describe two protocols for analyzing cell cycle status using flow cytometry. The first is based on the simultaneous analysis of proliferation specific marker (Ki-67) and cellular DNA content, which discriminates resting/quiescent cell populations (G0 cell) and quantifies cell cycle distribution (G1, S or G2/M, respectively). The second is based on differential staining of DNA and RNA through co-staining of Hoechst 33342 and Pyronin Y, which is also useful to identify G0 cells from G1 cells. Along with these methods for analyzing cell cycle status, we outline the basics of two additional methods for cell proliferation assays and recent updates of newly-developed fluorophores, which allows multiplex analysis of cell cycle status, cell proliferation and a gene of interest using flow cytometry.